NIR-activable charge transfer agents for synergistic photoimmunotherapy - Wang, Chu (2024)
The combination of photothermal therapy (PTT) and photodynamic therapy (PDT) has become an attractive tumor treatment modality, yet the facile design of photoimmunotheranostic agents with efficient near infrared (NIR) light-absorbing and immune-activating capabilities remains a tremendous challenge. Herein, we developed a NIR-activable organic charge transfer complex (CTC), with perylene (PER) as the electron donor and 4,5,9,10-tetrabromoisochromeno [6,5,4-def]isochromene-1,3,6,8-tetraone (Br4NDI) as the electron acceptor. Through further supramolecular assembly, the PER-Br4NDI nanoparticle (PBND NP) for spatiotemporally controlled photoimmunotherapy was constructed. The PBND NP exhibits superb NIR absorption, robust intermolecular charge transfer, and enhanced intersystem crossing. Upon NIR photoirradiation, the PBND NP effectively exerts photothermal and photodynamic effects with a remarkable photothermal conversion efficiency of 63.5 % and a high reactive oxygen species generation capability, which not only directly ablates primary tumors, but also dramatically suppresses distant tumor growth via promoted immunogenic cell death. Moreover, programmed cell death protein 1 antibody acts synergistically to block immune evasion and ultimately enhances cancer treatment efficacy. This work therefore sheds light on the design of organic CTCs for synergistic photoimmunotherapy.